Valorization of Lithium Extraction By-Products: Efficient Arsenic Adsorption Using Synthetic Aluminosilicates - Arancibia-Miranda, N; Arancibia-Miranda, N (ROYAL SOC CHEMISTRY, 2025)
The contamination of water resources by heavy metals, particularly arsenic, represents a critical environmental and public health challenge globally. Arsenic, originating from both geogenic processes and anthropogenic activities such as mining and industrial discharges, accumulates in aquatic systems, posing severe risks due to its toxicity. This study investigates the adsorption efficacy of synthetic aluminosilicates, specifically albite and nepheline, synthesized as by-products from an innovative lithium extraction process, for the remediation of arsenic-contaminated water. A comprehensive suite of characterization techniques, including XRD, SEM-EDS, FTIR, zeta potential, BET, adsorption kinetics, and isotherms, was employed to thoroughly evaluate the adsorbent materials. The research delineates the influence of solution pH and adsorbent dosage on the arsenic adsorption capacity of these materials. Comprehensive analyses of adsorption mechanisms and adsorbate-adsorbent interactions were conducted to elucidate the underlying processes. The results of this study demonstrate the potential of these synthetic aluminosilicates as efficient, low-cost adsorbents for arsenic removal, offering a viable and sustainable approach to address arsenic pollution in water resources. The innovative aspect of utilizing by-products from lithium extraction not only provides a novel solution for arsenic remediation but also adds value to industrial waste, promoting a circular economy. The findings have significant implications for the development of scalable and eco-friendly water treatment technologies, addressing both environmental sustainability and public health concerns.